2014
DOI: 10.1002/cctc.201400093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CO2 on the DeNOx Activity of a Small Pore Zeolite Copper Catalyst for NH3/SCR

Abstract: Exposure of CuSSZ13 to CO 2 at temperatures below 300 8C can deactivate its low-temperature deNOx activity during NH 3 /SCR, with the severity of deactivation being dependent on reaction temperature. The adsorption of NO on Cu 2 + ion is inhibited by CO 2 due to its competitive adsorption, while NH 3 adsorption on acidic sites of CuSSZ13 is largely unaffected by CO 2 , as evidenced by NO-and NH 3 -TPD in the presence of CO 2 . Under O 2 -rich conditions, CO 2 forms unidentate carbonates on Cu 2 + sites suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…The reasons might be due to the deposition of some nitrogenous species as the surface N content increased (see Table 1), where a similar phenomenon was also found in previous works. 34,37 All of the above results further confirmed the good stability of the catalysts during the SCR reaction in the presence of CO/CO 2 . The differences in SCR catalytic performance could not be attributed to the changes in physiochemical properties.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The reasons might be due to the deposition of some nitrogenous species as the surface N content increased (see Table 1), where a similar phenomenon was also found in previous works. 34,37 All of the above results further confirmed the good stability of the catalysts during the SCR reaction in the presence of CO/CO 2 . The differences in SCR catalytic performance could not be attributed to the changes in physiochemical properties.…”
Section: Resultssupporting
confidence: 66%
“…However, in addition to SO 2 , there still existed a certain amount of other interference components (acid gases, alkali, alkaline-earth, heavy metals, etc.) in the flue gas, which would poison the SCR catalysts and decrease denitration efficiency. Compared with the above-mentioned interference components, few studies regarding the influence of CO on the SCR reaction had been conducted . Normally, certain amounts of CO exist in the flue gases, especially those from industrial boilers and kilns.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [24] reported that CO 2 -induced deactivation in SCR was due to the adsorption of NH 3 by CO 2 , and supression of the formation of nitrates, which are a key reaction intermediate for NO x reduction. Yang et al [43] also reported that CO 2 may compete for the adsorbed NH 3 , which should be desirable for NO conversion.…”
Section: Comparison Of Co 2 and N 2 Atmosphere With Different Catalystsmentioning
confidence: 99%
“…Therefore, more understanding of NH 3 -SCR in the presence of an abundance of CO 2 is essential for the future development of SCR technology combined with oxy-fuel combustion processes. However, it is found that there are a few works investigating the influence of CO 2 on SCR [24,25]. For example, Kim et al [24] studied the effect of CO 2 on SCR using a small pore zeolite copper catalyst; and reported that CuSSZ13 catalyst can be deactivated by 10% CO 2 at low temperatures (<300˝C).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation